Particle size distribution measurement in a flowing aerosol using dynamic light scattering. (4th May 2021) - Mu, Tongtong; Shen, Jin; Wang, Mengjie; Thomas, John C; Zhu, Xinjun; Yuan, Xi; Liu, Wei; Sun, Xianming; Wang, Yajing; Han, Jinzhuang; Liu, Zhenming
Abstract: Simulated and experimental data were used to investigate the particle size distribution (PSD) recovery from a flowing aerosol via dynamic light scattering (DLS). It is found that, for a unimodal PSD, increasing the flow velocity leads to an increase in the error of the peak position, a decrease in the peak height and a broadening of the PSD. This is exacerbated for larger aerosol particles. For a bimodal PSD, the separation of the two peaks decreases and results in a single-peak PSD as the velocity increases. The effect of velocity on the measurement is similar to adding signal noise, which increases with the velocity. This effect is related to the measured aerosol particle size. The larger the particles, the lower the signal-to-noise ratio. By comparing DLS measurement results for flowing and non-flowing aerosol samples, it is possible to determine the maximum flow rate at which measurements can be usefully made.